Modelling and analysis of soil wetting patterns under surfrace drip irrigation - Naglic, Bostjan (Cranfield University, 2011)
Knowledge of the horizontal and vertical distances by which water spreads in soils under a point source is essential to the design of cost effective and efficient surface drip irrigation systems. The size of this wetting pattern is influenced by soil properties as well as emitter discharge rate and is a limiting factor determining the minimum number of emitters along drip lines. Numerical simulations were carried out with Hydrus-2D/3D to investigate the effects of volume of water applied, emitter discharge rate and initial soil moisture conditions on the dimension of wetting patterns under point source surface drip irrigation for a series of soils with different textures. In addition, the dimensions of the wetting patterns estimated with Hydrus-2D/3D for three soils and various flow rates were compared those observed with two-dimensional soil tank experiments. Finally, the wetting pattern dimensions obtained numerically were also compared to values estimated using a simple analytical model. Simulation results showed that at a given volume of applied water the wetted radius tended to be larger for fine-textured soils and smaller for coarse-textured soils. Conversely, the wetted depth was larger for coarse-textured soils and smaller for fine-textured soils. The wetted depth increased more than the wetted radius for increasing volumes of applied water. In the coarse-textured soils the wetting pattern was elongated in the vertical direction, but in fine-textured soils the wetting pattern lengths were about the same in both directions. Cont/d.